1995
DOI: 10.1126/science.7761835
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Gene Expression in Trypanosomes Mediated by a Prokaryotic Repressor

Abstract: An inducible expression system was developed for the protozoan parasite Trypanosoma brucei. Transgenic trypanosomes expressing the tetracycline repressor of Escherichia coli exhibited inducer (tetracycline)-dependent expression of chromosomally integrated reporter genes under the control of a procyclic acidic repetitive protein (PARP) promoter bearing a tet operator. Reporter expression could be controlled over a range of four orders of magnitude in response to tetracycline concentration, a degree of regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(182 citation statements)
references
References 40 publications
2
177
0
1
Order By: Relevance
“…In Vivo Depletion of IF2 by RNAi-Due to the availability of a tightly controlled tetracycline-inducible expression system (29), RNAi has become the method of choice to disrupt gene function in T. brucei (22,23). Thus, to investigate the function of IF2 by RNAi, we prepared a construct that contained a defined sequence of the IF2 gene in the sense, as well as the antisense, direction.…”
Section: Resultsmentioning
confidence: 99%
“…In Vivo Depletion of IF2 by RNAi-Due to the availability of a tightly controlled tetracycline-inducible expression system (29), RNAi has become the method of choice to disrupt gene function in T. brucei (22,23). Thus, to investigate the function of IF2 by RNAi, we prepared a construct that contained a defined sequence of the IF2 gene in the sense, as well as the antisense, direction.…”
Section: Resultsmentioning
confidence: 99%
“…In T. brucei regulated gene expression can be achieved using the system originally described by Wirtz and Clayton (1995), and subsequently modified to afford expression of highly toxic products (Wirtz et al+, 1999)+ The PARP promoter was rendered responsive to the tetracycline (Tet) repressor by addition of the Tet operator+ The appropriate constructs are transfected into a recipient cell line expressing the Tet repressor and are targeted to the nontranscribed ribosomal DNA spacer, which is a transcriptionally silent region of the genome+ To establish a regulated system for dsRNA expression, we constructed two insertion vectors, pLewFAT and pLewFATSH (Fig+ 1), both derivatives of pLew79 (Wirtz et al+, 1999)+ The important feature of pLewFAT and pLewFATSH is the presence of two copies of the a-tubulin 59 UTR, one in the sense and the other in the antisense orientation, relative to the PARP promoter+ These sequences are separated by a stuffer fragment of about 700 bp, which is necessary for propagation of the plasmids in bacteria due to instability of adjacent long inverted repeats (we refer to the tubulin sequences plus the stuffer fragment as the FAT DNA)+ We used the 59 UTR sequence of a-tubulin mRNA as a proof of principle, as we previously showed that dsRNA homologous to the a-tubulin 59 UTR efficiently targets mRNA degradation, whether transiently expressed from plasmid constructs or electroporated as synthetic dsRNA (Ngo et al+, 1998)+ Transcription of FAT DNA from the PARP promoter will generate an RNA molecule of about 1,000 nt, in which the a-tubulin sequences form a stem structure of 113 nt interrupted by a single-stranded loop consisting of the stuffer fragment sequence+ The difference between pLewFAT and pLewFATSH is the presence in pLewFAT of an expression cassette for the green fluorescent protein (gfp) upstream of the FAT DNA+ This is the same arrangement present in our prototypical construct pGFPFAT, which we have shown works well in transient expression assays+ pLewFAT and pLewFATSH were linearized in the rDNA targeting sequence and transfected by electroporation into 29+13+6 procyclic trypanosome cells+ Cells were selected for resistance to phleomycin and cloned on agarose plates+ Several cell lines derived from insertion of the pLewFAT construct, termed and 10 mg/mL+ Degradation of a-tubulin mRNA became evident at 0+5 mg/mL Tet and slightly increased at the higher concentrations tested+ The same RNA samples were also hybridized with a stuffer fragment-specific probe to detect transcripts derived from the FAT DNA (Fig+ 3)+ Clear hybridizing bands of about the expected size of 1,000 nt were detected at 0+5 mg/mL Tet and at higher concentrations+ Lastly, the cells were scored at the optical microscope for acquisition of the FAT phenotype+ FAT cells formed at 0+5 mg/mL Tet and higher concentrations, but very few if any were present at lower concentrations (data not shown)+ Thus, there appeared to be a threshold Tet concentration below which the FAT phenotype did not appear+ This threshold concentration correlated with the detection of the FAT phenotype, degradation of a-tubulin mRNA or the appearance of FAT DNA transcripts+…”
Section: Inducible Expression Of A-tubulin Dsrnamentioning
confidence: 99%
“…Culture Methods-Cultivation of 29-13 procyclic form (PCF) (28) and single marker bloodstream form (BSF) (29) trypanosomes derived from T. brucei Lister strain 427 was carried out as described previously (30). Cell growth was followed using a Beckman Coulter Z1 dual cell and particle counter.…”
Section: Methodsmentioning
confidence: 99%